2004
DOI: 10.1111/j.1744-7348.2004.tb00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Take‐all and grain yields in sequences of winter wheat crops testing fluquinconazole seed treatment applied in different combinations of years

Abstract: A seed treatment containing fluquinconazole as the only active ingredient was tested in sequences of up to six consecutive crops of winter wheat. It was applied or not applied in each year, and was tested in all possible combinations with treatments applied in previous years. Take-all was controlled effectively, and grain yield usually increased, when the disease intensity was moderate or severe in non-treated crops, but control of the most severe take-all did not result in acceptable yields or grain quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Fluquinconazole did not have any significant effect on the population structure of Ggt , measured by the percentage of the T2 mtSSU rRNA gene RFLP type, or the percentage of ITS4/ITS5 Hpa II B‐type, over 3 years (Bateman et al ., 2003; Freeman, 2004). Research has shown that fluquinconazole can be applied with economic effect on second or third wheat crops, but that a treated diseased crop should be followed by a break crop (or the following crop should be treated), and that treatment should not be applied during long sequences of wheat crops as it may disrupt development of the year‐to‐year epidemic and possibly take‐all decline (Bateman et al ., 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluquinconazole did not have any significant effect on the population structure of Ggt , measured by the percentage of the T2 mtSSU rRNA gene RFLP type, or the percentage of ITS4/ITS5 Hpa II B‐type, over 3 years (Bateman et al ., 2003; Freeman, 2004). Research has shown that fluquinconazole can be applied with economic effect on second or third wheat crops, but that a treated diseased crop should be followed by a break crop (or the following crop should be treated), and that treatment should not be applied during long sequences of wheat crops as it may disrupt development of the year‐to‐year epidemic and possibly take‐all decline (Bateman et al ., 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Take‐all disease and soil infectivity data are shown only for experiment CS/323, in which comparisons between nontreated and silthiofam‐treated crops are made. Other take‐all data from the experiments are presented elsewhere (Bateman et al ., 2003, 2004). The plant sample to assess take‐all was taken in early July 2002 at growth stage 73 (Zadoks et al ., 1974).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and percentage of diseased root axes were determined on plants sampled in March. Those sampled in July were scored for take‐all as follows (Bateman et al ., 2004): 1, slight disease with 1–10% of root system affected; 2, slight disease, 11–25% affected; 3, moderate disease, 26–50% affected; 4, moderate disease, 51–75% affected; 5, severe disease, 75% of root system affected. A take‐all index (TAI: 0–100) was calculated as the sum of the percentage of plants in each score category multiplied by its score value, divided by five.…”
Section: Methodsmentioning
confidence: 99%
“…Metalaxyl (Apron®) is the dominant product used for control of Pythium on germinating seeds, used in combination with either difenoconozole (Dividend®) or tebuconazole (Raxel®) for control of smuts (Smiley et al 1996). No work has been done in the Pacific Northwest with the seed treatment product fluquinoconazole, shown in Europe to have some benefit against take-all (Bateman et al 2004), but results from seed-treatment trails conducted with silthiofam, registered in Europe as Latitude® (Beale et al 1998) and shown to provide some level of take-all control used as seed treatment (Bailey et al 2005), has shown no benefit in the Pacific Northwest beyond the combination of agricultural practices described above (Cook, unpublished). In contrast, treatment of seeds with metalaxyl combined with either difenoconozole or tebuconazole produced average yield increases of 4-5% in continuous direct-seeded winter and spring wheat using the best agricultural practices described above .…”
Section: Role Of Pgpr In Take-all Declinementioning
confidence: 98%